2004
DOI: 10.1021/jo035749h
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Preparation of Optically Active Oxindoles Having a Stereogenic Quaternary Carbon Center at the C3 Position via the Lipase-Catalyzed Desymmetrization Protocol:  Effective Use of 2-Furoates for Either Enzymatic Esterification or Hydrolysis

Abstract: Both enantiomers of oxindoles 2a-h, having a stereogenic quaternary carbon center at the C3 position and a different N-protective group, were readily prepared by the lipase-catalyzed desymmetrization protocol. Thus, the transesterification of the prochiral diols 3a-h with 1-ethoxyvinyl 2-furoate 5 was catalyzed by Candida rugosa lipase to give (R)-(+)-2a-h (68-99% ee), in which the use of a mixed solvent, (i)Pr(2)O (diisopropyl ether)-THF, was crucial. The same lipase also effected the enantioselective hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…The absolute configuration of the major enantiomer of compounds 12 a-j was assigned by oxidation of the borylated oxindole 12 i to the known alcohol (R)-13 (Scheme 4). Comparison of the optical rotation of (R)-13 ([α] D = À 4.0, lit [α] D = À 8.5, > 99 : 1 e.r) and the chiral HPLC data (see SI) with the reported values [22] confirmed the (R)-configuration of this product. The alcohol (R)-13 has been previously reported as an intermediate in the synthesis of natural products (À )-esermethole and (À )phytostigmine, [23] offering a potential new route to this class of alkaloids.…”
Section: Entrysupporting
confidence: 55%
“…The absolute configuration of the major enantiomer of compounds 12 a-j was assigned by oxidation of the borylated oxindole 12 i to the known alcohol (R)-13 (Scheme 4). Comparison of the optical rotation of (R)-13 ([α] D = À 4.0, lit [α] D = À 8.5, > 99 : 1 e.r) and the chiral HPLC data (see SI) with the reported values [22] confirmed the (R)-configuration of this product. The alcohol (R)-13 has been previously reported as an intermediate in the synthesis of natural products (À )-esermethole and (À )phytostigmine, [23] offering a potential new route to this class of alkaloids.…”
Section: Entrysupporting
confidence: 55%
“…The Kita group further developed a desymmetric transesterification of oxindole diols 148 to construct quaternary oxindoles 149, using C. rugosa lipase (Scheme 46). 125 This represents an early example of highly enantioselective synthesis of quaternary oxindoles, a privileged scaffold widely present in many bioactive natural products and drugs; its catalytic synthesis is of great current interest. 126 The group found that N-protected oxindole diols 148 reacted with 1-ethoxyvinyl 2-furoate 146 in a mixed wet solvent of i Pr 2 O and tetrahydrofuran (THF) to give the (R)-enantiomer of quaternary oxindole 149 in good yield and excellent enantioselectivity.…”
Section: Desymmetric Transesterificationmentioning
confidence: 99%
“…For applications of oxindoles, see: Akai et al (2004); Gallagher et al (1985); Tokunaga et al (2001); Zaveri et al (2004). For applications of tetrahydrofurans, see: Garzino et al (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…The indole template is generally recognized as an important structure in medicinal chemistry. In particular oxindoles are important constituents of drugs (Akai et al, 2004). The Oxindole motif is present in the anti-Parkinson's drug ropinirole (Gallagher et al, 1985), in non-opioid receptor ligands (Zaveri et al, 2004) and in growth hormone secretagogues (Tokunaga et al, 2001).…”
Section: S1 Commentmentioning
confidence: 99%